PENERAPAN ASAS PRIMUM REMEDIUM DALAM TINDAK PIDANA PEMBAKARAN HUTAN YANG DILAKUKAN OLEH KORPORASI - Yori Demasto (Fakultas Hukum Universitas Tarumanagara, 2020)
Indonesia's forest fires occurring in Indonesia have disturbed many parties, not only the people and the country itself but also disturbing other countries, especially the neighboring countries affected and the losses resulting from the forest fires. Forest fires in Indonesia occur even every year in the last decade. This becomes a bad judgment against the government and Indonesian law. Forest fires occur because of many factors, one of which is forest fires conducted by corporations. It is inevitable that corporations are part of development activities, but corporations seem to take advantage of the development activities to exploit the environment. Corporations as forest fires that can cause massive and massive environmental damage. Government efforts in cracking down on forest burners are set out in the policy of law number 32 of 2009 on environmental protection and management. Law 32 of 2009 provides for strict provisions on the application of the principle of primum remedium on environmental crime